Silica Nanoparticles with Virus-Mimetic Spikes Enable Efficient siRNA Delivery In Vitro and In Vivo - Fu Jianye; Han Wenwei; Zhang Xue; Sun Yutong; Bhadane Rajendra; Wei Bo; Li Li; Yu Liangmin; Yang Jinbo; Rosenholm Jessica M; Salo-Ahen Outi MH; Fan Taojian; et al. (AMER ASSOC ADVANCEMENT SCIENCE, 2025)
Oligonucleotide-based therapy has experienced remarkable development in the past 2 decades, but its broad applications are severely hampered by delivery vectors. Widely used viral vectors and lipid nanovectors are suffering from immune clearance after repeating usage or requiring refrigerated transportation and storage, respectively. In this work, amino-modified virus-mimetic spike silica nanoparticles (NH2-SSNs) were fabricated using a 1-pot surfactant-free approach with controlled spike lengths, which were demonstrated with excellent delivery performance and biosafety in nearly all cell types and mice. It indicated that NH2-SSNs entered cells by spike-dependent cell membrane docking and dynamin-dependent endocytosis. The positively charged spikes with proper length on the surface can facilitate the efficient encapsulation of RNAs, protect the loaded RNAs from degradation, and trigger an early endosome escape during intracellular trafficking, similarly to the cellular internalization mechanism of virions. Regarding the fantastic properties of NH2-SSNs in nucleic acid delivery, it revealed that nanoparticles with solid spikes on the surface would be excellent vehicles for gene therapy, presenting self -evident advantages in storage, transportation, modification, and quality control in large-scale production compared to lipid nanovectors.